New Insights Into Energy Substrate Utilization and Metabolic Remodeling in Cardiac Physiological Adaption - Shi, Xiaomeng; Qiu, Hongyu (Frontiers in Physiology, 2022)
Cardiac function highly relies on sufficient energy supply. Perturbations in myocardial energy metabolism play a causative role in cardiac pathogenesis. Accumulating evidence has suggested that modifications of cardiac metabolism are also an essential part of the adaptive responses to various physiological conditions in the heart to meet the specific energy demand. In the review, we summarized current studies on general profiling of cardiac metabolism, focusing on the new insights into the energy substrate utilization in cardiomyocytes. We also discussed the most recent findings regarding cardiac metabolic remodeling and their associated mechanisms under physiological conditions, including exercise, cardiac development, and aging. Studying the impact of the metabolic profile in the heart in these conditions can contribute to understanding the significance of metabolic regulation in the heart during physiological adaption and the maladaptive metabolic changes with associated cardiac pathogenesis, opening the avenues to exploring novel therapeutic strategies in cardiac diseases.